Pleomorphic liposarcoma: A cytologic study of five cases. Issue 2 (21st March 2014) - Dodd, Leslie G.; "Sara" Jiang, Xiaoyin; Rao, Kathleen; Bui, Marilyn M.
<x xml:space="preserve">Abstract</x> Pleomorphic liposarcoma represents one of the rarest variants of liposarcoma. It has a poor prognosis and unlike other variants of liposarcoma, lacks a molecular or genetic signature. Histologic studies of pleomorphic liposarcoma have defined this lesion as a high grade sarcoma, which contains a variable number of lipoblasts. We describe the cytologic features of five cases of pleomorphic liposarcoma, all of which had histologic confirmation. We consistently identified numerous lipoblasts as well as micro and macrovesicular fat vacuoles in the background of cellular, pleomorphic sarcomatoid neoplasms. The appearance of the aspirates differs substantially form other variants of liposarcoma. Diagn. Cytopathol. 2015;43:138–143. © 2014 Wiley Periodicals, Inc.